Lichen planus and associated psychosomatic disorders - I. Yu. Dorozhenok; E. S. Snarskaya; V. G. Shenberg (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The urgency is due to a wide range of psychosomatic comorbidity lichen planus (LP). Objective: to determine the clinical relationships of the LP with comorbid psychosomatic disorders. The present prospective clinical study 93 (58 women, 35 men; middle age. 47, 6 years) of patients with LP predominantly dermal localization clinical-dermatological (using scales: the index of clinical symptoms -ICS and questionnaire dermatology quality of life index - DIQL), psychopathological, experimental-psychological, clinical and follow-up, statistical methods. Identified and clinically verified psychogenic manifestation of skin lesions in 28 (30.1%); nosogenic reactions (F43) 56 (60,2%); recurrent depression (F33) - in 9 (9.7%) cases. Defined clinical the relationship of various forms of the LP, the nature of the flow, severity, location and extent of the severity and structure of comorbid psychosomatic disorders.